Immune Evasion Mechanisms of Entamoeba histolytica: Progression to Disease - Begum, Sharmin; Quach, Jeanie; Chadee, Kris (Frontiers in Microbiology, 2015)
Entamoeba histolytica (Eh) is a protozoan parasite that infects 10% of the world’s population and results in 100,000 deaths/year from amebic dysentery and/or liver abscess. In most cases, this extracellular parasite colonizes the colon by high affinity binding to MUC2 mucin without disease symptoms, whereas in some cases, Eh triggers an aggressive inflammatory response upon invasion of the colonic mucosa. The specific host-parasite factors critical for disease pathogenesis are still not well characterized. From the parasite, the signature events that lead to disease progression are cysteine protease cleavage of the C-terminus of MUC2 that dissolves the mucus layer followed by Eh binding and cytotoxicity of the mucosal epithelium. The host mounts an ineffective excessive host pro-inflammatory response following contact with host cells that causes tissue damage and participates in disease pathogenesis as Eh escapes host immune clearance by mechanisms that are not completely understood. Ameba can modulate or destroy effector immune cells by inducing neutrophil apoptosis and suppressing respiratory burst or nitric oxide (NO) production from macrophages. Eh adherence to the host cells also induce multiple cytotoxic effects that can promote cell death through phagocytosis, apoptosis or by trogocytosis (ingestion of living cells) that might play critical roles in immune evasion. This review focuses on the immune evasion mechanisms that Eh uses to survive and induce disease manifestation in the host.